A Histological and Clinical Study of MatriDerm® Use in Burn Reconstruction - Dickson, Kathryn; Lee, Kwang Chear; Abdulsalam, Abdulrazak; Amirize, Ezekwe; Kankam, Hadyn K N; ter Horst, Britt; Gardiner, Fay; Bamford, Amy; Hejmadi, Rahul K; Moiemen, Naiem (Journal of burn care & research, 2023)
Abstract Dermal substitutes are well established in the reconstructive ladder. MatriDerm® (Dr. Otto Suwelack Skin & Health Care AG, Billerbeck, Germany) is a single-layer dermal substitute composed of a bovine collagen (type I, III, and V) and elastin hydrolysate, that allows for immediate split-thickness skin grafting (SSG). The aim of this study was to histologically characterize the integration of MatriDerm® when used during burns surgery reconstruction. Eight subjects with nine burn scars and one acute burn wound underwent reconstruction with MatriDerm® and an immediate SSG. MatriDerm® integration and skin graft take were assessed with serial biopsies performed at weeks 1, 2, 3, and 4 and months 2, 3, 6, 9, and 12. Biopsies were assessed with standard special stains and immunohistochemistry, and representative slides were imaged with a transmission electron microscope. Patient satisfaction and clinical scar outcome were assessed with the Vancouver Scar Scale and a patient questionnaire. Histological analysis showed similar stages of wound healing as shown in other dermal templates but on a different timescale. There is early evidence of vascularization and an inflammatory infiltrate in the first 2 weeks. MatriDerm® is resorbed earlier than other dermal substitutes, with evidence of resorption at week 3, to be completely replaced by a neodermis at 2 months. The use of MatriDerm® in reconstruction with immediate skin grafting is supported histologically with early evidence of vascularization to support an epidermal autograft. Future histological studies may help further characterize the ideal dermal substitute.